Pengaruh Motivasi Kerja Terhadap Retensi Mitra Grab Driver di Kabupaten Karawang - Azhi Fadlih Saputra; Enjang Suherman; Rena Augia Putrie (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Technological advances in the transportation sector have driven economic growth in Indonesia, one of which is the presence of application-based transportation platforms such as Grab. This research aims to analyze the influence of work motivation on the retention of Grab Driver partners in Karawang Regency. Work motivation is the main factor that can influence the sustainability of the partnership between drivers and companies. Factors such as physical needs, security and safety needs, social needs, the need for recognition according to one's abilities and the need for self-actualization. This research uses a quantitative approach with a survey method of 96 respondents who are Grab Driver partners in Karawang Regency. Data were analyzed using simple linear regression techniques with the help of the SPSS version 30 program. The research results showed that work motivation had a positive and significant influence on partner retention. Partially, work motivation has a significant effect on the retention of grab driver partners in Karawang district. Simultaneously, work motivation and other supporting factors contribute to the retention of Grab Driver partners, with a significant influence based on the results of statistical analysis. The implications of this research theoretically reveal that there is a positive and significant relationship between work motivation and retention of Grab Driver partners in Karawang Regency.